Third order nonlinear optical property of Bi2Se3 - Lu, Shunbin (2013)
The third order nonlinear optical property of Bi2Se3, a kind of topological insulator (TI), has been investigated under femto-second laser excitation. The open and closed aperture Z-scan measurements were used to unambiguously distinguish the real and imaginary part of the third order optical nonlinearity of the TI. When excited at 800 nm, the TI exhibits saturable absorption with a saturation intensity of 10.12 GW/cm2 and a modulation depth of 61.2%, and a giant nonlinear refractive index of 10 -14 m2/W, almost six orders of magnitude larger than that of bulk dielectrics. This finding suggests that the TI: Bi2Se 3 is indeed a promising nonlinear optical material and thus can find potential applications from passive laser mode locker to optical Kerr effect based photonic devices.